Students Mastery Level on Introduction to Economic Subject in Industrial Engineering Program of South Aceh Polytechnic - Devi Satria Saputra; Khairuman Man (Jurnal Inotera, 2019)
An introduction toeconomics is a course taught in Industrial Engineering Department of South Aceh Polytechnic, the course is taught for second year students as a compulsory subject that must be mastered by students. The writerwho has experiencedthe teaching in Industrial Engineering Department of South Aceh Polytechnic found that there were many students who found it difficult to master the courseespecially in understanding the demandsand offers. Therefore, the writer conducted research on students' mastery in introductory to the economics courseespecially in demands and offered topic of Industrial Engineering Department students. The purpose of this study was to determine the level of student mastery on the demands and offers, various mistakes made by students in understanding the concepts and various factors that cause these mistakes. The research is a qualitative descriptive study. The subject of this study was the second year students of Industrial Engineering Department. Data collection techniques are carried out by conducting tests and interviews. Data obtained and converted into predetermined mastery criteria, and then the data will be analyzed using a percentage formula.